(3TQM CQLhRI GHf SjfG aj GdWHs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedjc GdhGMO QH GdSeGhGJ GdYdi GdeGLO s
(3BNQgG (B:s
(3GdYbd eG GSJbGe ai JUhQg hacQg , hUM ai JPcQg s
(3bWYg ef GdTQMs
(3JHOC HChd GdcJGHs
(3hgj eJOGNdI ZjQ eQJHgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs